Outcome evaluation of dipeptidyl peptidase 4 (DPP4) inhibitors and its combination on glycemic control of type 2 diabetes mellitus patients at Putrajaya Hospital / Nurhamizah Noor Rahim - Noor Rahim, Nurhamizah (2016)
Introduction: Dipeptidyl Peptidase 4 Inhibitor (DPP4-I) is a relatively new antidiabetic agent, hence the study on glycemic outcome in Malaysian population is still lacking. Currently, there is no study conducted in Putrajaya Hospital to examine the outcome of DPP4-I and its combination on glycemic control of Type 2 Diabetes Mellitus (T2DM) patients, response towards DPP4-I and predictors for HbA1c reduction. Objective: To evaluate outcome at week 16, 32 and 52; to determine ADR arises from DPP4-I; and to evaluate predictors for HbA1c reduction at week 52. Method: A retrospective observational study was conducted on 184 T2DM patients that were prescribed with DPP4-I. Paired t-test, ANOVA and linear regression analysis were conducted accordingly. Results: 39.1% of study subjects managed to attain HbA1c value ≤7.0% after 52 weeks of therapy with DPP4-I and its combinations. The mean HbA1c reduction was 0.7% compared to baseline. 70.7% were responsive to the DPP4-I treatment with age at the initiation of DPP4-I, mean HbA1c at baseline and week 52 and mean number of antidiabetics prescribed at baseline and week 52 were significantly different between subgroups. Unresponsive subgroup attained only 0.2% HbA1c reduction at around week 16 compared to significant HbA1c reduction attained by responsive group. 2.7% adverse drug reaction related to DPP4-I was reported. Baseline HbA1c values, HbA1c changes at around week 16 and age were found to be the predictors for HbA1c reduction. Conclusion: The addition of DPP4-I demonstrated moderate glycemic reduction to T2DM patients. However, factors such as adherence towards antidiabetics, diet, physical activity and insulin intensification that was not assessed in this study may also influence this effect.